Pentingnya Pemahaman Pancasila sebagai Dasar dan Ideologi Negara - Sitti Uswatun Hasanah (LPPM IKIP PGRI Pontianak, 2012)
Pancasila is an ideology or worldview contents basic concepts about life aspired to by the people of Indonesia. It containts fundamental thoughts and ideas about life is good, according to the value they have. These values have been purivied in five basic. So, as an ideology or a philosophy of life, Pancasila is the crystallization of the values held and sourced from the nation of Indonesia.